Entrepreneurial Tournaments: Towards Disclosing the Rivalry Process Among Corporate Entrepreneurs - Mohammad Zarei (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The notons and motvatons of inter-organisatonal rivalries among employees have to some extent been highlighted by classical theories of management such as tournament theory. However, employees’ and entrepreneurs’ compettons are fundamentally diﬀerent in patern. Based on the doctrine of entrepreneurship, entrepreneurial compettons are essental for a productve economy. Even so, there have been few in-depth holistc atempts to understand the rivalry process among corporate entrepreneurs. During the last three decades, various fragmented studies have been conducted from diﬀerent standpoints to clarify the process of corporate entrepreneurship (CE). Nevertheless, considerable room remains for developing a model of the rivalry process with respect to entrepreneurial actvites within large and complex organisatons. Hence, the main contributon of the research can be claimed as investgatng and formulatng the rivalry process. For this purpose, a systematc qualitatve grounded theory methodology (GTM) was used. During a fve-month period, corporate entrepreneurs from one of the chief Iranian research insttutes were systematcally interviewed. Based on the research results, in additon to endorsing the existence of such a rivalry process among corporate entrepreneurs, the GTM model extends the literature of CE by examining the previously unaddressed part of the process, i.e., disclosing the corporate entrepreneurs’ implemented strategies, among other blocks of the theory.